Responses of Arctic cyclones to biogeophysical feedbacks under future warming scenarios in a regional Earth system model. (14th June 2021) - Akperov, Mirseid; Zhang, Wenxin; Miller, Paul A; Mokhov, Igor I; Semenov, Vladimir A; Matthes, Heidrun; Smith, Benjamin; Rinke, Annette
Abstract: Arctic cyclones, as a prevalent feature in the coupled dynamics of the Arctic climate system, have large impacts on the atmospheric transport of heat and moisture and deformation and drifting of sea ice. Previous studies based on historical and future simulations with climate models suggest that Arctic cyclogenesis is affected by the Arctic amplification of global warming, for instance, a growing land-sea thermal contrast. We thus hypothesize that biogeophysical feedbacks (BF) over the land, here mainly referring to the albedo-induced warming in spring and evaporative cooling in summer, may have the potential to significantly change cyclone activity in the Arctic. Based on a regional Earth system model (RCA-GUESS) which couples a dynamic vegetation model and a regional atmospheric model and an algorithm of cyclone detection and tracking, this study assesses for the first time the impacts of BF on the characteristics of Arctic cyclones under three IPCC Representative Concentration Pathways scenarios (i.e. RCP2.6, RCP4.5 and RCP8.5). Our analysis focuses on the spring- and summer time periods, since previous studies showed BF are the most pronounced in these seasons. We find that BF induced by changes in surface heat fluxes lead to changes in land-sea thermal contrast and atmospheric stability. This, in turn, noticeably changes the atmospheric baroclinicity and, thus, leads to a change of cyclone activity in the Arctic, in particular to the increase of cyclone frequency over the Arctic Ocean in spring. This study highlights the importance of accounting for BF in the prediction of Arctic cyclones and the role of circulation in the Arctic regional Earth system.